SURGICAL OPERCULECTOMY PROCEDURE IN THE TREATMENT OF PERICORONITIS (CASE REPORTS) - Veronica Septnina Primasari (Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2023)
Background: pericoronitis is an inflammation of the soft tissue around the crown of the erupting or partially impacted mandibular third molar and usually occurs at the age of 20-29 years. This soft tissue is known as the operculum. Pericoronitis is caused by food debris trapped in the operculum and challenging to clean, causing inflammation that can be acute or chronic. Operculectomy is a surgical removal of the operculum and can be performed using a scalpel, laser, and electrocautery. Case report: case 1: A 22-year-old female patient complained of frequent pain in the left posterior gingiva, and food was often trapped in the gingiva. Clinical examination showed inflammation in the operculum of an erupted tooth 38. Scaling, the first phase of treatment, is performed to remove plaque and calculus, followed by operculectomy. Case 2: A 20-year-old female patient was referred from the orthodontic department with complaints of difficulty opening her mouth and pain in the left cheek and neck; the patient has been given antibiotics and analgesics. From the clinical examination, tooth 38 erupted with inflammation of the operculum. The patient was given antibiotics and follow-up analgesics to relieve the acute phase, and scaling was done; then, an operculectomy was performed after the patient could open her mouth. Conclusion: operculectomy with a scalpel is a procedure that can be performed in treating pericoronitis to remove the operculum; this makes it easier for patients to maintain oral hygiene.